French Science Communication on YouTube: A Survey of Individual and Institutional Communicators and Their Channel Characteristics - Debove, Stéphane; Füchslin, Tobias; Louis, Tania; Masselot, Pierre (Frontiers in Communication, 2021)
Science videos on YouTube attract millions of viewers each month, but little is known about who the content producers are, how they work and what their motivations and qualifications are. Here, we analyze the characteristics of 622 French YouTube science channels and 70,795 science videos in French, and complement this analysis with a survey of 180 of these youtubers. We focus on three questions: who are the science communicators (sociodemographics, resources, and goals), what are the characteristics of their channels, and are there differences between institutional and non-institutional communicators. We show that French science communicators on YouTube are mostly young men, highly qualified and usually talking about their topic of expertise. Many of them do not earn enough money to make a living out of this activity and have to use personal money to run their channels. At the same time, many are not interested in making this activity their main source of income. Their main goal is to share science and stimulate curiosity, as opposed to teach and entertain. While a small number of channels account for most of the views and subscribers, together they are able to cover a lot of scientific disciplines, with individuals usually focusing on a couple of fields and institutions talking about more diverse subjects. Institutions seem to have less success on YouTube than individuals, a result visible both in the number of subscribers and engagement received in videos (likes and comments). We discuss the potential factors behind this discrepancy, such as the lack of personality of institutional channels, the high number of topics they cover or the fact that institutions usually have an additional goal compared to individuals: to present and promote the institution itself.